2009
DOI: 10.1017/s0022215109004277
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hyperbaric oxygen therapy in management of sudden hearing loss

Abstract: Considering the cost of hyperbaric oxygen therapy and its inconvenience to patients, this treatment should only be considered in patients suffering sudden hearing loss if there are contraindications to standard medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
1
22
0
1
Order By: Relevance
“…Three studies, conluded that the addition of HBO did not have a significant impact on the prognosis [19–21]. Satar et al found a hearing gain in favour of the HBO group.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies, conluded that the addition of HBO did not have a significant impact on the prognosis [19–21]. Satar et al found a hearing gain in favour of the HBO group.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used salvage therapies for sudden hearing loss are HBO therapy and intratympanic steroid therapy [17][18][19][20][21] . A comparison of these two methods was recently described [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…Cekin et al [26] administered 1 mg/kg oral steroid and HBO therapy to 36 patients and oral steroid therapy alone to 21 patients and did not Wnd any statistically signiWcant diVerence between hearing results.…”
Section: Discussionmentioning
confidence: 99%